'A feeling which it is impossible for Englishmen to understand': Booker T. Washington and Anglo‐American Rivalries. Issue 376 (23rd June 2021) - Webb, Clive
Abstract: African American educator and activist Booker T. Washington visited Britain in 1899 and 1910. This article uses these transatlantic encounters to reassess conventional notions of the late nineteenth and early twentieth centuries as an era of rapprochement between Britain and the United States rooted in racial ideas of Anglo‐Saxon supremacy. It shows how the visits exacerbated a rift between the two countries over the issue of race. At a time when the United States had started to eclipse their own country economically, Britons used their enthusiastic reception of Washington as a means to reassert their claims to moral superiority over Americans whom they accused of failing to fulfil their paternalist obligations to other races. Race was therefore the cause of conflict as much as cooperation in Anglo‐American relations.